2021
DOI: 10.1371/journal.ppat.1009600
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi’s sarcoma-associated herpesvirus vFLIP promotes MEndT to generate hybrid M/E state for tumorigenesis

Abstract: Kaposi sarcoma (KS) is an angioproliferative and invasive tumor caused by Kaposi sarcoma-associated herpesvirus (KSHV). The cellular origin of KS tumor cells remains contentious. Recently, evidence has accrued indicating that KS may arise from KSHV-infected mesenchymal stem cells (MSCs) through mesenchymal-to-endothelial transition (MEndT), but the transformation process has been largely unknown. In this study, we investigated the KSHV-mediated MEndT process and found that KSHV infection rendered MSCs incomple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The receptors for KSHV entry into endothelial, epithelial, and mononuclear cells and macrophages, such as EPHA2, integrins, DC-SIGN, and xCT, as well as related entry mechanisms, have been intensively investigated [reviewed in ( 14 , 15 )]. In contrast, the receptors for KSHV infection of MSCs had been largely ignored because its pathogenetic significance was not clear until recently when increasing evidence emerged showing that KSHV-infected MSCs may be the origin or progenitor of KS spindle cells ( 7 , 8 , 10 , 46 ) and that pediatric osteosarcoma, a MSC-originated malignancy, is reported to be associated with KSHV infection ( 4 ). Although numerous KSHV receptors have been identified, the expression of these receptors in MSCs is very low (fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The receptors for KSHV entry into endothelial, epithelial, and mononuclear cells and macrophages, such as EPHA2, integrins, DC-SIGN, and xCT, as well as related entry mechanisms, have been intensively investigated [reviewed in ( 14 , 15 )]. In contrast, the receptors for KSHV infection of MSCs had been largely ignored because its pathogenetic significance was not clear until recently when increasing evidence emerged showing that KSHV-infected MSCs may be the origin or progenitor of KS spindle cells ( 7 , 8 , 10 , 46 ) and that pediatric osteosarcoma, a MSC-originated malignancy, is reported to be associated with KSHV infection ( 4 ). Although numerous KSHV receptors have been identified, the expression of these receptors in MSCs is very low (fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the heterogeneity of spindle-shaped cells has led to the hypothesis that KS may originate from mesenchymal stem cells (MSCs) or precursors of vascular cells (6). As more and more evidence (7)(8)(9)(10) was unearthed, this hypothesis has been gaining ground and forming relatively well-developed perspectives that KS may originate from KSHV-infected pluripotent MSCs and KSHV infection transforms MSCs to KS cells through an mesenchymal-to-endothelial transition process.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al recently found that KSHV can promote an intermediate state of mesenchymal‐to‐endothelial differentiation of subpopulations of periodontal ligament stem cells (PDLSCs), correlated with the existence of KSHV‐positive spindle cells in Kaposi sarcoma lesions displaying a mesenchymal/endothelial phenotype 14 . In this line, our sequencing transcriptomic analysis showed the existence of subpopulations of KSHV‐infected hMSC growing in a KS‐like proangiogenic environment expressing oncogenic viral genes and oncogenic host genes together with endothelial and mesenchymal differentiation markers, pointing to a role of these cells in KS initiation and progression through the mesenchymal‐to‐endothelial differentiation axis.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Wang et al has recently shown that KSHV infection of periodontal ligament stem cells (PDLSCs) significantly upregulates the expression of chemokine receptors and promotes the migration and settlement of MSCs at wound sites 13 . Similarly, Chen et al demonstrated that KSHV infection of MSCs initiates an incomplete MEndT process, generating hybrid mesenchymal/endothelial (M/E) state cells, which are abundant in KS lesions 14 …”
Section: Introductionmentioning
confidence: 99%
“…Wang et al recently showed that KSHV infection of periodontal ligament stem cells (PDLSCs) significantly upregulated the expression of several chemokine receptors and promoted MSC migration and settlement in the wound sites [11]. Chen et al showed that KSHV infection of MSCs initiates an incomplete MEndT process and generates hybrid mesenchymal/endothelial (M/E) state cells and that KS lesions contained a large number of tumor cells with a M/E state [12]. We have previously shown that MSC culture conditions favor viral production with decreased proliferation of infected cells.…”
Section: Introductionmentioning
confidence: 99%